Social Accounts and the Business Enterprise Sector of the National Economy (Book). - Cannon, Arthur M.; Murphy, Mary E. (The Accounting Review, 1950)
Abstract Reviews the book "Social Accounts and the Business Enterprise Sector of the National Economy," by F. Sewell Bray.